Genetic Analysis of Mitochondrial Ribosomal Proteins and Cognitive Aging in Postmenopausal Women - Mozhui, Khyobeni; Snively, Beverly M.; Rapp, Stephen R.; Wallace, Robert B.; Williams, Robert W.; Johnson, Karen C. (Frontiers in Genetics, 2017)
Genes encoding mitochondrial ribosomal proteins (MRPs) have been linked to aging and longevity in model organisms (i.e., mice, C. elegans). Here we evaluated if the MRPs have conserved effect on aging traits in humans. We utilized data from 4504 participants of the Women’s Health Initiative Memory Study (WHIMS) who had both longitudinal cognitive data and genetic data. Two aging phenotypes were considered: (1) gross lifespan (time to all-cause mortality), and (2) cognitive aging (longitudinal rate of change in modified mini-mental state scores). We tested genetic association with variants in 78 members of the MRP gene family. Genetic association tests were done at the single nucleotide polymorphism (SNP) level, and at gene-set level using two distinct procedures (GATES and MAGMA). We included SNPs in APOE and adjusted the tests for the APOE-ε4 allele, a known risk factor for dementia. The strongest association signal is for the known cognitive aging SNP, rs429358, in APOE (p-value = 5 x 10 -28 for cognitive aging; p-value = 0.03 for survival). We found no significant association between the MRPs and survival time. For cognitive aging, we detected SNP level association for rs189661478 in MRPL23 (p-value < 9 x 10-6). Furthermore, the gene-set analysis showed modest but significant association between the MRP family and cognitive aging. In conclusion, our results indicate a potential pathway-level association between the MRPs and cognitive aging that is independent of the APOE locus. We however did not detect association between the MRPs and lifespan.